2021
DOI: 10.1038/s41598-021-95869-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs3750920 polymorphism in TOLLIP with clinical characteristics of fibrosing interstitial lung diseases in Japanese

Abstract: TOLLIP polymorphism has been implicated in the development and prognosis of idiopathic pulmonary fibrosis (IPF), mainly in whites. However, ethnic differences in the characteristics of other interstitial pneumonia (non-IPF) subtypes are unclear. We evaluated the association between the rs3750920 genotype and the clinical characteristics of Japanese patients with fibrosing interstitial lung diseases (ILD). We genotyped 102 patients with fibrosing ILD (75 IPF and 27 non-IPF patients) and analyzed the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In another retrospective study of patients with IPF and IPAF, rs3750920 T/T showed an increased frequency in the positive ANA group, in which NAC exposure seemed to be bene cial for transplant-free survival [35]. In a Japanese population study, the frequency of the minor T allele of rs3750920 was low in patients with brotic ILD, especially in non-IPF patients, which might be an indicator of better survival in these patients [14]. In an inception cohort study on early rheumatoid arthritis (RA), TOLLIP rs111521887 was associated with pulmonary brosis in RA [36].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In another retrospective study of patients with IPF and IPAF, rs3750920 T/T showed an increased frequency in the positive ANA group, in which NAC exposure seemed to be bene cial for transplant-free survival [35]. In a Japanese population study, the frequency of the minor T allele of rs3750920 was low in patients with brotic ILD, especially in non-IPF patients, which might be an indicator of better survival in these patients [14]. In an inception cohort study on early rheumatoid arthritis (RA), TOLLIP rs111521887 was associated with pulmonary brosis in RA [36].…”
Section: Discussionmentioning
confidence: 95%
“…Dysregulation of TOLLIP is associated with various diseases, such as Parkinson's disease, Alzheimer's disease, in ammatory bowel disease, myocardial hypertrophy, and idiopathic pulmonary brosis [9][10][11][12][13]. Several studies have focused on the association between genetic variants of TOLLIP and susceptibility, treatment response, and the progression of patients with CTD-ILD [14][15]. However, the location of TOLLIP in the lung tissue of patients with CTD-ILD has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…TogoVar is becoming recognized as shared infrastructure data. The purposes for its use are variant prioritization 34 , determination of whether a variant of interest is known or unknown 35 , and comparison of allele frequencies in TogoVar with those of disease groups or non-Japanese populations 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%